Globalizaç\~ao, desglobalizaç\~ao e o Brasil - Renato Baumann Neves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The last three decades have witnessed important changes in transportation, communication and data processing, with effects over productive processes, trade flows and the international movement of capital. From the viewpoint of developing economies this led to the recommendation of adhering to this process as a tool to foster economic and social development. As for the Brazilian economy, its participation in the process of globalization has been limited so far, except for the movement of capital. Its share in total merchandise trade is low, as is the number of preferential trade agreements. It has not been possible to reduce the 'economic distance' towards the high-income economies.
Keywords: F13; F21; F43; F50; O57; 330; globalization; deglobalization; economic development; convergence